Pemasaran Produk Kembang Tahu Menggunakan Marketing Mix - Dewanti , Agilia Putri Ayu (Universitas Dehasen Bengkulu, 2024)
The marketing mix paradigm, in its famous version of the 4Ps, went all the way through the evolution of marketing theory: from the marketing concept, through relationship marketing, to digital economy, being object of discussion both in academic literature and managerial practice. If it is a fact that the 4Ps marketing mix is a milestone of marketing theory, it is also true that the evolution of business contexts has created, in many fields, the need to review the